REKONSTRUKSI PENDIDIKAN ISLAM DALAM MEMBUDAYAKAN PERDAMAIAN - Ruslan Ruslan; Luthfiyah Luthfiyah (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
This article discussed Islamic education studies in cultivated the peace. This article is based on social reality which is complete with conflict and violence that contradictive with Islamic basic doctrine abaout happiness and peacefulness.conflict and violence are not only influenced by one factor, but also they are influenced by multifactor like economy, culture, and politic. Violence is social problem is not hopped appear in human life, including violence by jihad or war in Allah road. Like wise the violence by the J. Galtung, that include with the cultural violence. So, the Islamic education is hoped to be the important element in cultivated the peace. In this contect, the Islamic education can programmed peace education as effort cultivation the peace in all aspect human life.